Drivers of assemblage‐wide calling activity in tropical anurans and the role of temporal resolution. Issue 3 (20th December 2020) - Sugai, Larissa S. M.; Silva, Thiago S. F.; Llusia, Diego; Siqueira, Tadeu
Abstract: Temporal scale in animal communities is often associated with seasonality, despite the large variation in species activity during a diel cycle. A gap thus remains in understanding the dynamics of short‐term activity in animal communities. Here we assessed calling activity of tropical anurans and addressed how species composition varied during night activity in assemblages along gradients of local and landscape environmental heterogeneity. We investigated 39 anuran assemblages in the Pantanal wetlands (Brazil) with passive acoustic monitoring during the peak of one breeding season, and first determined changes in species composition between night periods (early, mid and late) using two temporal resolutions (1‐ and 3‐hr intervals). Then, we addressed the role of habitat structure (local and landscape heterogeneity variables from field‐based and remote sensing metrics) and ecological context (species richness and phylogenetic relatedness) in determining changes in species composition (a) between night periods and (b) across days. Nocturnal calling activity of anuran assemblages varied more within the 1‐hr resolution than the 3‐hr resolution. Differences in species composition between early‐ and late‐night periods were related to local habitat structure and phylogenetic relatedness, while a low variation in compositional changes across days was associated with low‐heterogeneous landscapes. None of these relationships were observed using the coarser temporal resolution (3 hr). Our findings on the variation of calling activity in tropical anuran assemblages suggest potential trade‐offs mediated by fine‐temporal partitioning. Local and landscape heterogeneity may provide conditions for spatial partitioning, while the relatedness among co‐signalling species provides cues on the ecological overlap of species with similar requirements. These relationships suggest a role of niche dimensional complementarity on the structuring of these anuran assemblages over fine‐temporal scales. We argue that fine‐temporal differences between species in breeding activity can influence the outcome of species interaction and thus, addressing temporal scaling issues can improve our understanding of the dynamics of animal communities. Abstract : The authors show that tropical anuran communities have widespread short‐term dynamics related to ecological gradients at both local and landscape scales. Their findings argue for trade‐offs between fine temporal dynamics and other complementary niche dimensions in animal communities.